2003
DOI: 10.1074/jbc.m301673200
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Trafficking and Activation of Tumor Necrosis Factor-α-converting Enzyme in Cell Mutants Defective in Protein Ectodomain Shedding

Abstract: Protein ectodomain shedding is a specialized type of regulated proteolysis that releases the extracellular domain of transmembrane proteins. The metalloprotease disintegrin tumor necrosis factor-␣-converting enzyme (TACE) has been convincingly shown to play a central role in ectodomain shedding, but despite its broad interest, very little is known about the mechanisms that regulate its activity. An analysis of the biosynthesis of TACE in mutant cell lines that have a gross defect in ectodomain shedding (M1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 37 publications
0
49
0
Order By: Relevance
“…This pattern of inhibitor specificity is consistent with the possibility that the metalloproteinase responsible for AP-ATE-CD8 shedding is TACE (30). To further test this possibility, we examined shedding in CHO-M1 cells, a CHO variant in which TACE biogenesis is defective (31). Both AP-ATE-CD8 and AP-PAR1, a construct in which alkaline phosphatase was fused to the N-terminal exodomain of human PAR1 six codons N-terminal to the thrombin cleavage site (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This pattern of inhibitor specificity is consistent with the possibility that the metalloproteinase responsible for AP-ATE-CD8 shedding is TACE (30). To further test this possibility, we examined shedding in CHO-M1 cells, a CHO variant in which TACE biogenesis is defective (31). Both AP-ATE-CD8 and AP-PAR1, a construct in which alkaline phosphatase was fused to the N-terminal exodomain of human PAR1 six codons N-terminal to the thrombin cleavage site (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, it was recently shown that biosynthesis of TACE, but not that of several other surface metalloproteinases including ADAM10, was defective in a mutant cell line, CHO-M2. CHO-M2 and the mutant cell line used in our study, CHO-M1, are of the same genetic complementation group (with respect to shedding of the TACE substrate, TGF-␣) and share a lack of properly processed TACE and inability to shed numerous known TACE substrates (31). Attempts to more directly confirm the role of TACE in regulated PAR1 shedding using TACE-knockout cells (4) were not interpretable.…”
Section: Discussionmentioning
confidence: 99%
“…2B). The stimulated shedding of numerous proteins, including several TACE substrates, in response to agents such as phorbol esters is absent in the M2 CHO cell line (5,10,70,72). We therefore assessed the ability of this cell line to shed p75 NTR when stimulated.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we used wild-type CHO cells and the previously described M2 mutant CHO cells, which are defective in the metalloprotease-mediated shedding of several transmembrane proteins (5). The mutation in the M2 cells inactivates the TNF␣ convertase (TACE, ADAM17) 2 and abolishes the stimulated shedding of all TACE substrates examined to date (69,70). Cells transiently transfected with either a control vector or a plasmid encoding for rat p75 NTR were pulse-labeled.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown recently that this mutant cell line has a specific defect that prevents the activation of TACE, but not other metalloproteases (45). Therefore, to determine whether active TACE participates in the shedding of betaglycan induced by pervanadate, we analyze the effect of pervanadate on the M1 mutant and on the wild type CHO cells that were stably transfected with HA-tagged betaglycan (HABG construct, see Fig.…”
Section: Pervanadate Activates the Shedding Of Betaglycan-ectodo-mentioning
confidence: 99%